Effects of the professional identity development programme on the professional identity, job satisfaction and burnout levels of nurses: A pilot study. Issue 6 (29th April 2014) - Sabancıogullari, Selma; Dogan, Selma
Abstract : The aim of this study was to evaluate the effects of the Professional Identity Development Program on the professional identity, job satisfaction and burnout levels of registered nurses. This study was conducted as a quasi‐experimental one with 63 nurses working in a university hospital. Data were gathered using the Personal Information Questionnaire, the Professional Self Concept Inventory, Minnesota Job Satisfaction Inventory and the Maslach Burnout Inventory. The Professional Identity Development Program which consists of ten sessions was implemented to the study group once a week. The Program significantly improved the professional identity of the nurses in the study group compared to that of the control group. During the research period, burnout levels significantly decreased in the study group while those of the control group increased. The programme did not create any significant differences in the job satisfaction levels of the nurses. The programme had a positive impact on the professional identity of the nurses. It is recommended that the programme should be implemented in different hospitals with different samples of nurses, and that its effectiveness should be evaluated.